Norcrassin A, a novel C16 tetranorditerpenoid, and bicrotonol A, an unusual dimeric labdane-type diterpenoid, from the roots of Croton crassifolius. Issue 10 (20th February 2018) - Zhang, Zhan-Xin; Wu, Pei-Qian; Li, Hui-Hong; Qi, Feng-Ming; Fei, Dong-Qing; Hu, Qiao-Ling; Liu, Ying-Hong; Huang, Xiao-Ling
Abstract : Norcrassin A (1 ), a novel C16 tetranorditerpenoid, featuring a new carbon skeleton, and bicrotonol A (2 ), an unusual dimeric labdane-type diterpenoid, were isolated from Croton crassifolius . Abstract : A novel C16 tetranorditerpenoid, norcrassin A (1 ), and an unusual dimeric labdane-type diterpenoid, bicrotonol A (2 ), were isolated from the roots of Croton crassifolius . Norcrassin A (1 ) featured a new carbon skeleton with an unprecedented 5/5/5/6 tetracyclic system. Bicrotonol A (2 ) possessed an unusual tetrahydroxypyran ring linkage connecting two labdane diterpenoid monomers. The structures of all compounds, including the absolute configuration, were elucidated by the interpretation of their NMR spectroscopic data, high resolution mass spectrometry, and single-crystal X-ray diffraction. A plausible biosynthetic pathway of1 is proposed. The anti-Alzheimer's Disease (AD) activities of1 and2 are also evaluated using the AD pathological model.